Peningkatan Kemampuan Berbahasa Indonesia Dengan Media Gambar Sederhana Jembatan Kata Pada Siswa Kelas V SDN 37 Cakranegara - Huduni, Awanisul; Hidayati, Nurlia; Adinda, Dayita Wahyu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
Language skills are necessary for all students because language is the most important tool for communicating with others. The problems in this study are: 1) Can the use of word connecting pictures improve the Indonesian language skills of fifth grade students at SDN 37 Cakranegara? 2) Is there an improvement in Indonesian through media of word bridge images in class V students of SDN 37 Cakranegara after using word bridge media? The type of research used is Classroom Action Research. The results of the study stated that there was a significant increase in Indonesian language skills by using word bridge images as media for fifth grade students at SDN 37 Cakranegara.